AGAMA SIAP SAJI DI KALANGAN MILLENIAL - Wardah Wardah (UIN ANTASARI BANJARMASIN, 2020)
AbstractMillennial comes from English, Millennium which means a thousand years. Millennials are described as a generation that cannot be far from technology users including